Factors Influencing of School Type, Parental Educational Background, Gender, and Age on the English Language Speaking Proficiency of Chinese College Students - Pei, Jianting; Pamintuan, Cavin F. (International Journal of Language Education, 2024)
English, as an international language of communication, plays a crucial role in the development of global economic exchanges. In China, where English serves as a second language, the improvement of college students' English language speaking proficiency faces numerous challenges due to the lack of authentic English communication environments. However, there has been a lack of in-depth research on the relationship between Chinese college students' English language speaking proficiency and factors such as school background. This study utilized multiple linear regression to analyze data from the 2021 China General Social Survey. It aimed to investigate the relationship between college students' English language speaking proficiency and various factors, including different types of high school experiences, parental educational backgrounds, gender differences, and age disparities. The findings revealed that college students who attended provincial-level and municipal-level key high schools demonstrated higher English language speaking proficiency. Additionally, paternal educational background had a more significant impact on the English language speaking proficiency of offspring compared to maternal educational background. Furthermore, female students exhibited higher English speaking proficiency levels than male students. Moreover, English speaking proficiency showed an inverted "U"-shaped trend with age, peaking at 22.5 years old. Based on the research results, recommendations were proposed to balance the educational resources of different types of high schools and to reform English teaching in universities. These suggestions aim to provide robust evidence for the formulation of educational policies to meet the growing demand for English learning in China.